2017
DOI: 10.1039/c7cp03632a
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemistry and stability of metastable corundum-type In2O3

Abstract: To account for the explanation of an eventual sensing and catalytic behavior of rhombohedral In 2 O 3 (rh-In 2 O 3 ) and the dependence of the metastability of the latter on gas atmospheres, in situ electrochemical impedance spectroscopic (EIS), Fourier-transform infrared spectroscopic (FT-IR), in situ X-ray diffraction and in situ thermogravimetric analyses in inert (helium) and reactive gases (hydrogen, carbon monoxide and carbon dioxide) have been conducted to link the gas-dependent electrical conductivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…59,60 Additionally, it is known that in strongly reductive atmospheres, such as CO and H 2 , the allotrope transformation proceeds following the same pathwayrh-In 2 O 3 → c-In 2 O 3 , meanwhile the reverse transformation happens only at high energy input. 61 Extrapolating the observation, one of the processes occurred during the catalytic run is recrystallization of amorphous S13B). Finally, the third and more peculiar component found to be formed is a mixed metal carbide, Co 3 InC 0.75 (Figure 3D).…”
Section: Resultsmentioning
confidence: 92%
“…59,60 Additionally, it is known that in strongly reductive atmospheres, such as CO and H 2 , the allotrope transformation proceeds following the same pathwayrh-In 2 O 3 → c-In 2 O 3 , meanwhile the reverse transformation happens only at high energy input. 61 Extrapolating the observation, one of the processes occurred during the catalytic run is recrystallization of amorphous S13B). Finally, the third and more peculiar component found to be formed is a mixed metal carbide, Co 3 InC 0.75 (Figure 3D).…”
Section: Resultsmentioning
confidence: 92%
“…24 The process of phase trans- formation in In 2 O 3 has been a focus of attention, since the different polymorphs show specific properties that directly affect the performance of the desired applications. 25 Koch et al 26 observed from adsorption measurements that rh-In 2 O 3 exhibits predominantly Lewis acidic surface sites compared to bcc-In 2 O 3 ; thus, the cubic structure presented a superior CO 2 selectivity in methanol steam reforming. Wu et al 27 investigated the photocatalytic activities of rh-In 2 O 3 and bcc-In 2 O 3 nanostructures and obtained the highest efficiency for degradation of tetracycline using rh-In 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The capillaries containing the sample powder can be connected to a mass-flow controlled gas atmosphere, which allows for time varying, well-controlled gas-atmospheres. This set-up creates excellent data in the realm of catalysis and solid state chemistry (e.g., Mattox et al [48], Köck et al [49]). Figure 10.…”
Section: Resistive and Lamp Heatingmentioning
confidence: 99%